Change in type-2 biomarkers and related cytokines with prednisolone in uncontrolled severe oral corticosteroid dependent asthmatics: an interventional open-label study. Issue 8 (2nd April 2019) - Busby, John; Holweg, Cecile T J; Chai, Akiko; Bradding, Peter; Cai, Fang; Chaudhuri, Rekha; Mansur, Adel H; Lordan, James Laurence; Matthews, John G; Menzies-Gow, Andrew; Niven, Robert; Staton, Tracy; et al.
Abstract : Type-2 biomarkers and related cytokines (IL-5, IL-13), lung function and asthma symptoms were measured in 44 poorly-controlled severe oral corticosteroid (OCS)-dependent asthmatics for up to 88 days after a 7-day prednisolone boost (0.5 mg/kg). High-dose OCS reduced median blood eosinophils (−60 cells/µl; 95% CI −140 to 10), periostin (−8.4 ng/mL; −11.6 to –2.8), FeNO (−19.0 ppb; −28.5 to –4.0), IL-5 (−0.17 pg/mL; −0.28 to –0.08) and IL-13 (−0.15 pg/mL; −0.27 to –0.03). There were small improvements in mean FEV1 (0.16 L; 0.05 to 0.27) and (Asthma Control Questionnaire) ACQ-7 score (0.3; 0.0 to 0.7). Study measures returned to baseline 1-month postintervention. Following rescue OCS, 1 month is sufficient before using type-2 biomarkers to guide long-term treatment. Trial registration number: NCT01948401 .